Islamic Transformational Leadership Training in Optimising Educational Management at Madrasah Tsanawiyah Nurul Wafa - M. Kurma Nur Faifatur R; Samsul Arifin; Ahmad Rifdur Rohman (ASSUNNAH PRESS, 2026)
Madrasah Tsanawiyah Nurul Wafa faces significant challenges in strengthening leadership capacity, which directly affects the effectiveness of institutional governance, teacher professionalism, and organisational culture. The prevailing instructive and hierarchical leadership patterns have constituted a primary obstacle to promoting institutional innovation and collaboration. This community service programme aimed to: (1) deliver structured training on the Islamic Transformational Leadership model; (2) analyse the impact of the training on madrasah governance, teacher professionalism, and organisational culture; and (3) identify the barriers and enabling factors in its implementation. The programme was conducted in partnership with Madrasah Tsanawiyah Nurul Wafa, involving 18 participants comprising the madrasah principal, two vice-principals, three field coordinators, and twelve teachers. The programme was designed using a qualitative-based action research approach, in which the training simultaneously functioned as a community service intervention and an object of systematic evaluation. Implementation methods included interactive lectures, focused group discussions, leadership role-playing simulations grounded in Bass-Avolio's four dimensions (idealized influence, inspirational motivation, intellectual stimulation, individualized consideration), and a two-week post-training observational mentorship. Data were collected through participatory observation, in-depth interviews, and documentation studies, and were analysed using a descriptive-qualitative approach. Training outcomes demonstrated measurable positive changes: the principal began adopting more participatory decision-making patterns; teachers exhibited increased confidence in proposing curriculum innovations; and eleven programme innovation ideas were spontaneously generated by participants during the closing session. The primary barriers identified were resistance among senior teachers and budgetary constraints for sustained programmes. This programme demonstrates that integrating Islamic values — amanah, musyawarah, ta'awun — with a transformational leadership approach effectively strengthens leadership capacity and educational management in madrasah settings.